Pengaruh Literasi Keuangan dan Persyaratan Kredit terhadap Minat Meminjam di PT. Permodalan Nasional Madani (PNM) Cabang Sungai Pagu - Fuji Mustika; Asmy Febri Tama; Riza Eka Putri (Strata Business Review, 2023)
This study aims: (1) to see an overview of financial literacy, credit requirements and interest in borrowing at PNM. (2) to determine the effect of financial literacy on the interest in borrowing at PNM (3) to determine the effect of credit requirements on the interest in borrowing at PNM. (4) to determine the effect of financial literacy and credit requirements on interest in borrowing at PNM. Data analysis used Multiple Regression Analysis with the computer program SPSS for window 25. The results showed that: (1) financial literacy was in good criteria with an average score of 4.15 and a TCR of 83.1%, credit requirements were in good criteria with an average score of 4.43 and a TCR of 89 %, interest in borrowing is in very good criteria with an average score of 4.52 and a TCR of 90.4%, (2) financial literacy has no significant effect on interest in borrowing in PNM with a significance level (H01) of 0.432 > 0, 05 and t count value of 0.794 < from t table which is 1.990, (3) credit requirements have a significant effect on interest in borrowing at PNM with a significance level (Ha2) of 0.000 <0.05 and t count value of 6.974 > of 1.990, (4 ) financial literacy and credit requirements together have a significant effect on the interest in borrowing at PNM with a significance level (Ha3) of 0.000 <0.05 and an calculated F value of 294.177 > from F table which is 3.12.